2001
DOI: 10.1054/bjoc.2001.1804
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of human prostatic epithelial cells with bone marrow endothelium: binding and invasion

Abstract: The second commonest cause of cancer death in the Western world is attributed to prostate cancer (Jensen et al, 1990). It is well documented that prostatic carcinoma shows a predilection to metastasize to the bone marrow (Jacobs, 1983). Metastatic prostate cancer remains an incurable disease and as such, is a massive clinical problem. There is clearly a need to elucidate the factors underlying the spread of prostate cancer, particularly to the skeleton.It has been suggested that the bone marrow microenvironmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
79
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 34 publications
3
79
0
Order By: Relevance
“…To examine this phenomenon more closely, with particular reference to binding and invasion, we used the GFP-transfected PC-3 cell line in conjunction with BMEC using confocal microscopy. We found that most of the PC3-GFP cells bound within 60 min and further to Scott et al (2001), we found that they had a marked tendency to bind at endothelial junctional regions (86.2677.12%; P ¼ 0.003). Figure 1A shows three PC3-GFP cells at their binding sites after 60 min in contact with the BMEC.…”
Section: Measurement Of Pc3-gfp Invasion Through Bmecmentioning
confidence: 51%
See 4 more Smart Citations
“…To examine this phenomenon more closely, with particular reference to binding and invasion, we used the GFP-transfected PC-3 cell line in conjunction with BMEC using confocal microscopy. We found that most of the PC3-GFP cells bound within 60 min and further to Scott et al (2001), we found that they had a marked tendency to bind at endothelial junctional regions (86.2677.12%; P ¼ 0.003). Figure 1A shows three PC3-GFP cells at their binding sites after 60 min in contact with the BMEC.…”
Section: Measurement Of Pc3-gfp Invasion Through Bmecmentioning
confidence: 51%
“…We have previously developed models allowing the study of the interactions between malignant prostate epithelial cells and endothelial or BMS layers (Lang et al, 1997(Lang et al, , 1998Scott et al, 2001). We have developed these models to target the blood/BMS endothelial barrier specifically, thereby allowing the visualisation not just of the sites of binding but also of the prostate epithelial invasive process.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations